2013
DOI: 10.5005/jp-journals-10024-1406
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Serum Copper and Zinc Levels in Oral Submucous Fibrosis: An Atomic Absorption Spectroscopic Study

Abstract: Background and objectives: Biochemical derangements of microelements although reported in oral cancer is poorly understood in oral submucous fibrosis (OSMF). Hence, the present study was carried out to estimate and compare the serum copper and zinc levels among different histopathological stages of OSMF with that of healthy controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Similar contradictory observations have been reported by previous studies. 20,21 23 We found males were mostly involved in areca nut product consumption and these findings are consistent with Okade et al 13 who reported 96.6% male population in their recent study. Similar male proclivity was reported by a previous study.…”
Section: Discussionsupporting
confidence: 90%
“…Similar contradictory observations have been reported by previous studies. 20,21 23 We found males were mostly involved in areca nut product consumption and these findings are consistent with Okade et al 13 who reported 96.6% male population in their recent study. Similar male proclivity was reported by a previous study.…”
Section: Discussionsupporting
confidence: 90%
“…They even concluded that early evaluation of serum zinc levels contributes to early diagnosis of disease. 16 The present study used atomic absorption spectroscopy for evaluation of salivary levels which is expensive and may not available in all clinical setups but has exceptional accuracy. We further recommend the correlation of salivary levels with the clinical staging of OSMF.…”
Section: Discussionmentioning
confidence: 99%
“…Both the biological sample and gender did not affect the difference in the levels of trace elements between OSF and healthy controls. The level of plasma/serum/saliva Zn in OSF participants has been evaluated in numerous investigations [ 4 , 23 , 26 , 27 , 29 – 31 , 35 , 37 , 55 ]. Only four of these did not report lower Zn levels in OSF patients [ 12 , 28 , 34 , 63 ].…”
Section: Discussionmentioning
confidence: 99%